2021
DOI: 10.1007/s00526-020-01886-3
|View full text |Cite
|
Sign up to set email alerts
|

Orlicz–Minkowski flows

Abstract: We study the long-time existence and behavior for a class of anisotropic non-homogeneous Gauss curvature flows whose stationary solutions, if they exist, solve the regular Orlicz–Minkowski problems. As an application, we obtain old and new existence results for the regular even Orlicz–Minkowski problems; the corresponding $$L_p$$ L p version is the even $$L_p$$ L … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Another main issue is the study of the problem on the existence of the prescribed polynomial of the principal curvature radii of the hypersurface. Urbas [29], Gerhart [15], Chow-Tsai [12], Bryan-Ivaki-Scheuer [4] shed light on the convergence for the flow with the speed of symmetric polynomial of the principal curvature radii of the hypersurface. In this paper, we consider a class of generalized fully nonlinear curvature flow of convex hypersurfaces M t parameterized by smooth map X(•, t) :…”
Section: Introductionmentioning
confidence: 99%
“…Another main issue is the study of the problem on the existence of the prescribed polynomial of the principal curvature radii of the hypersurface. Urbas [29], Gerhart [15], Chow-Tsai [12], Bryan-Ivaki-Scheuer [4] shed light on the convergence for the flow with the speed of symmetric polynomial of the principal curvature radii of the hypersurface. In this paper, we consider a class of generalized fully nonlinear curvature flow of convex hypersurfaces M t parameterized by smooth map X(•, t) :…”
Section: Introductionmentioning
confidence: 99%
“…The Gauss curvature flow was first introduced and studied by Firey [11] to model the shape change of worn stones. Since then, many scholars have found that using curvature flow to study the hypersurfaces is a very effective tool, such as solving the Minkowski-type problems and geometric inequalities in convex geometric analysis etc., see e.g., [2,3,5,7,8,17,18,27,29] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the geometric flows in [3,5,7,8,29], the flow we construct in the present paper is more complex due to its inclusion of functions φ, |∇Ψ| and γ(t), which is reflected in the fact that priori estimates are more difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…The Orlicz-Minkowski problem [23] is related to the case when G = t n /n and ϕ is a non-homogeneous function. Solutions to the Orlicz-Minkowski problem can be found in, e.g., [2,9,26,35,40,45,57,58,59,63,64]. When G = t q /n and ϕ(t) = t p for 0 = p ∈ R, the general dual Orlicz-Minkowski problem reduces to the L p dual Minkowski problem [50]; contributions to this problem can be seen in, e.g., [3,10,11,14,33,38,41,55].…”
Section: Introductionmentioning
confidence: 99%